Penggunaan Telemonitoring untuk Mengurangi Readmisi pada Pasien Gagal Jantung - Kapriana Tanty Natalia; Denissa Faradita Aryani; Tuti Herawati (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the effectiveness of telemonitoring on the incidence of readmission in patients with heart failure. The method used in this study is a literature review focusing on articles published in the last five years and English, with the target population being patients aged over 18 years. The article search strategy uses online databases, namely "ScienceDirect," "ProQuest," "Sage," and "Scopus," using keywords and Boolean Operators. The results showed that using a telemonitoring system in most articles proved effective in reducing readmissions in heart failure patients. This difference occurs due to differences in the number of samples and the length of time of the study. In conclusion, telemonitoring is effective in reducing readmission in heart failure patients compared to those who receive regular care. Keywords: Heart failure, Rehospitalization, Telemonitoring